APPROPRIATION OF COMPEIITlVE INTELUGENCE PRACTICES FOR THE ARTlCULATION 10 THE MARKEl OF SMALL SCALE RURAL AGROENTERPRlSE NETWORKS - Plazas Tenorio, Adolfo León; Pabon Ortiz, Heidy; Rebolledo, Sandra Patricia (Cuadernos de Administración, 2007)
Satisfy the requirements of an increasingly global and exigent demand is a great challenge for any company, but much more for the rural agroenterprises of the country due the low entrepreneurship ofthese productive units and the difficult sih¡ation facing the state support. With this participatory research-action proposal co fmanced by Colciencias, ACAC, CREPIC and University of Cauca It is intended that the rural agroenterprise networks adopt systematic practices near the Competi tive Intelligence Influencing in a better articulatíon with the market. Tbe proposed innovation is to identify tbe Sporadic practices on market Monitoring and decision making tbat are currently performed by the rural producers, With habits tbat allow them to become a daily discipline; Moreover, since sorne aspects of the rc are an unattainable complexity for anetwork, The proposal will issue recommendations to guide the regional-national institutional support in this component.